β Property in W hyperbolic Spaces - FAN Liying; SONG Jingjing; WANG Ping (Journal of Harbin University of Science and Technology)
In this paper, the definition of β property is given in βWhyperbolic space, and then the definition of β module in β space is applied to prove its approximate compactness, so it has normal structure; Secondly, the nonnullative properties of β space are proved Finally, the fixed point existence problem of asymptotic average nonexpansion mapping in β space is discussed